Entropy, information and doubly stochastic transformations - Daboul, Jamil [UNESP] (Elsevier, 1991)
I analyze two inequalities on entropy and information, one due to von Neumann and a recent one to Schiffer, and show that the relevant quantities in these inequalities are related by special doubly stochastic matrices (DSM). I then use generalization of the first inequality to prove algebraically a generalization of Schiffer's inequality to arbitrary DSM. I also give a second interpretation to the latter inequality, determine its domain of applicability, and illustrate it by using Zeeman splitting. This example shows that symmetric (degenerate) systems have less entropy than the corresponding split systems, if compared at the same average energy. This seemingly counter-intuitive result is explained thermodynamically. © 1991.